Controlling protein orientation in vacuum using electric fields - Marklund, E; Ekeberg, T; Moog, M; Benesch, J; Caleman, C (American Chemical Society, 2017)
Single-particle imaging using X-ray free-electron lasers is an emerging technique that could provide high-resolution structures of macromolecules in the gas phase. One of the largest difficulties in realizing this goal is the unknown orientation of the individual sample molecules at the time of exposure. Preorientation of the molecules has been identified as a possible solution to this problem. Using molecular dynamics simulations, we identify a range of electric field strengths where proteins become oriented without losing their structure. For a number of experimentally relevant cases we show that structure determination is possible only when orientation information is included in the orientation-recovery process. We conclude that nondestructive field orientation of intact proteins is feasible and that it enables a range of new structural investigations with single-particle imaging.